Dyslexia: A Bibliometric and Visualization Analysis - Wu, Yanqi; Cheng, Yanxia; Yang, Xianlin; Yu, Wenyan; Wan, Yuehua (Frontiers in public health, 2022)
Dyslexia is a disorder characterized by an impaired ability to understand written and printed words or phrases. Epidemiological longitudinal data show that dyslexia is highly prevalent, affecting 10–20% of the population regardless of gender. This study aims to provide a detailed overview of research status and development characteristics of dyslexia from types of articles, years, countries, institutions, journals, authors, author keywords, and highly cited papers. A total of 9,166 publications have been retrieved from the Social Sciences Citation Index (SSCI) and Science Citation Index Expanded (SCI-E) from 2000 to 2021. The United States of America, United Kingdom, and Germany were the top three most productive countries in terms of the number of publications. China, Israel, and Japan led the Asia research on dyslexia. University of Oxford had the most publications and won first place in terms of h-index. Dyslexia was the most productive journal in this field and Psychology was the most used subject category. Keywords analysis indicated that “developmental dyslexia,” “phonological awareness,” children and fMRI were still the main research topics. “Literacy,” “rapid automatized naming (RAN),” “assessment,” “intervention,” “meta-analysis,” “Chinese,” “executive function,” “morphological awareness,” “decoding,” “dyscalculia,” “EEG,” “Eye tracking,” “rhythm,” “bilingualism,” and “functional connectivity” might become the new research hotspots.